Interannual variability of ground surface thermal regimes in Livingston and Deception islands, Antarctica (2007–2021) - Pablo, M. A. de (2023)
The absence of vegetation in most ice-free areas of Antarctica makes the soil surface very sensitive to atmosphere dynamics, especially in the western sector of the Antarctic Peninsula, an area within the limits of the permafrost zone. To evaluate the possible effects of regional warming on frozen soils, we conducted an analysis of ground surface temperatures (GSTs) from 2007 to 2021 from different monitoring sites in Livingston and Deception islands (South Shetlands archipelago, Antarctica). The analysis of the interannual evolution of the GST and their daily regimes and the freezing and thawing indexes reveals that climate change is showing impacts on seasonal and perennially frozen soils. Freezing Degree Days (FDD) have decreased while Thawing Degree Day (TDD) have increased during the study period, resulting in a balance that is already positive at the sites at lower elevations. Daily freeze–thaw cycles have been rare and absent since 2014. Meanwhile, the most common thermal regimes are purely frozen – F1 (daily temperatures < = 0.5C), isothermal – IS (ranging between 0.5C to +0.5C), and purely thawed – T1 (> = +0.5C). A decrease in F1 days has been observed, while the IS and T1 days increased by about 60 days between 2007 and 2021. The annual number of days with snow cover increased between 2009 and 2014 and decreased since then. The GST and the daily thermal regimes evolution point to general heating, which may be indicative of the degradation of the frozen soils in the study area.